2019
DOI: 10.17509/ijost.v4i2.18185
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Cruising Fixed Wing Mini Unmanned Aerial Vehicle Performance Optimization

Abstract: The applications of unmanned aerial vehicles have been extended through the recent decades and they are utilized for both civil and military applications. The urge to utilize unmanned aerial vehicles for civil purposes has elevated researchers and industries interest towards the mini unmanned aerial vehicle (MUAV) category due to its suitable configurations and capabilities for multidisciplinary civil purposes. This study is an effort to further enhance the aerodynamic efficiency of MUAVs through a parametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Based on our previous studies (Eftekhari & Al-Obaidi, 2019;Eftekhari et al, 2020;Al-Obaidi et al, 2021;Al-Qassar et al, 2021a;Al-Qassar et al, 2021b), in the current study, the main contribution can be highlighted by the following points:…”
Section: Introductionmentioning
confidence: 55%
“…Based on our previous studies (Eftekhari & Al-Obaidi, 2019;Eftekhari et al, 2020;Al-Obaidi et al, 2021;Al-Qassar et al, 2021a;Al-Qassar et al, 2021b), in the current study, the main contribution can be highlighted by the following points:…”
Section: Introductionmentioning
confidence: 55%
“…The lift and drag coefficients for the investigated wings are shown in figure 10. It is observed that the lift coefficient for configurations with a 7% span ratio is almost the same as the Alpine wing [16]. Also, it is observed that increasing the Alula span results in a gradual reduction in lift and this can be explained by the higher pressure generated between Alula and the wing surface.…”
Section: Alula Effectmentioning
confidence: 84%
“…Other techniques and methodologies can be pursued to extend this study for future work (Yung et al, 2016;Eftekhari & Al-Obaidi, 2019;Eftekhari et al, 2020;Kulshreshtha & Al-Obaidi, 2020;Al-Obaidi, 2021;Ali et al, 2020;Al-Obaidi, A. S. M. et al, 2021b;Eftekhari et al, 2023).…”
Section: Introductionmentioning
confidence: 99%